STUDI TENTANG PERBAIKAN JATUH TEGANGAN DI TIANG UJUNG JARINGAN TEGANGAN RENDAH PADA PT.PLN UP3 AREA SAMARINDA - Nur Rani Alham; Restu Mukti Utomo; Hilmansyah Hilmansyah; Angga Wahyu Aditya; Muslimin Muslimin; Abdul Mubarak (Lembaga Penelitian Universitas Balikpapan, 2022)
Abstract— Electric power distribution system is one of the systems in electric power that has an important role that is directly related to the user of electric energy. In the distribution system must have the appropriate reliability of the standards applied but in reality the distribution of electric power distribution is not appropriate, such as falling voltage commonly called drop voltage that reaches the consumer. This is caused by several factors so that the quality of existing electricity is not optimally beneficial and can even cause damage to electrical equipment. In phase S, from the analysis of calculations and measurements made by the author based on basic theory, conclusions can be drawn as follows. In calculations and measurements in phaseS R and T the voltage fall is caused by the length of the delivery. In phase S, when viewed from the calculation and measurement of voltage fall due to the length of the delivery and other factors, namely the cable connection is not perfect. From the data obtained by the author of the voltage fall at the GNK 383 Distribution Substation is not constant because the load changes the use of electrical energy by different consumers The voltage fall at the GNK 383 Distribution Substation occurs at night because the load usage activity by consumers is very high.